Quality response of tomato cherry (Lycopersicum cerasiforme mil ) to the use of Sonic Bloom technology and various foliar fertilizer - Sri Wuryani; Heti Herastuti; Dedik Supriyanto (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2014)
The objective of this research was to determine the appropriate foliar fertilizer in the use of Sonic Bloom Technology to the yield quality of tomato cv. cherry (Lycopersivcum cerasoforme Mill.) Split plot design with two factors was set in this experiment. The main plot was Sonic Bloom Technology (with and without Sonic Bloom) and the sub plot was four kinds of foliar fertilizer (Sonic Bloom Fertilizer, Growmore, Bayfolan, Hyponex). The quality parameters observed were number of open stomata, weight and diameter of tomato, color, moisture, content of total sugar and ascorbic acid . The result of this research showed that there was no interaction between Sonic Bloom Technology utilization and foliar fertilizer. Almost all quality parameters showed that treatments of Sonic Bloom are significantly higher than treatments without Sonic Bloom, except for color and moisture. Meanwhile, all quality parameters were not influenced by the kind of foliar fertilizer.Keywords : Sonic Bloom, Foliar Fertilizer, Cherry Tomato